The History, Legalization and Potentials of Psilocybin-Assisted Psychotherapy - Heilman, Jeffery (Journal of Scientific Exploration, 2023)
The potential benefits and deficits of the chemical compound psilocybin, particularly when paired with psychotherapeutic interventions, have been increasingly apparent topics of interest in social, academic, and scientific circles. The unusual nature of psilocybin poses many questions in Western culture. Three of them, which will be discussed in the following review, are (1) What is psilocybin? (2) What is psilocybin-assisted psychotherapy? and (3) What are the potential advantages and disadvantages of psilocybin-assisted psychotherapy? Psilocybin-assisted psychotherapy is an innovative treatment that has not had the opportunity to be well-studied; as a result, the topic is currently shrouded in controversy and confusion. However, a recent series of clinical trials and research projects involving psilocybin-assisted interventions have yielded significant and beneficial results; indeed, additional trials are under way. The interventions studied include the treatment of end-of-life anxiety, depression, and existential distress in patients with terminal cancer, tobacco addiction, and treatment-resistant major-depressive disorder. Investigation into the known history, uses, relevance, and therapeutic effects of psilocybin-assisted psychotherapy require a careful inquiry, as these interventions are making an unavoidable and profound impact on contemporary American psychological culture as well as society in general. The current review attempts to describe psilocybin’s shamanic roots, known history, legal controversy, psychotherapy, and contemporary neuroscience research.